2009
DOI: 10.1002/ajhb.20961
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐globin gene cluster haplotypes in Afro‐Uruguayans from two geographical regions (South and North)

Abstract: The beta-globin gene cluster haplotypes were identified in 52 and 40 chromosomes from two Afro-Uruguayan populations located in the South and North of the country, respectively. In both regions, the 5' haplotype 2 (+ - - - -), characteristic of non-African populations, was the most frequent, reflecting a strong process of admixture in Afro-Uruguayans (0.355 and 0.262, respectively). The haplotypes 3 (- - - - +) and 4 (- + - - +), characteristics of African sub-Saharan populations, present inverse frequencies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Studies in self-defined African descendants, however, have presented very different results: African genes contribute nearly half of the ancestry to these populations, while Native American contributions vary from 15% in the south to 25% in the northeast and 42% in the south (Sans et al , 2002, Da Luz et al , 2010). …”
Section: The Genetic/genomic Approach To Interethnic Admixturementioning
confidence: 99%
“…Studies in self-defined African descendants, however, have presented very different results: African genes contribute nearly half of the ancestry to these populations, while Native American contributions vary from 15% in the south to 25% in the northeast and 42% in the south (Sans et al , 2002, Da Luz et al , 2010). …”
Section: The Genetic/genomic Approach To Interethnic Admixturementioning
confidence: 99%
“…When we consider other diseases, a clear excess of European genetic ancestry was detected in melanoma patients on chromosome 16 [37], which is expected for this type of cancer [38]. Moreover, other diseases, such as hemoglobinopathies or diabetes, showed an increased representation of non-European mutations, indicating the genetic contribution of Native American or African populations as expected [39][40][41].…”
Section: Discussionmentioning
confidence: 93%
“…Our study suggested 5’β-haplotype might not be sufficient in providing the full range of genetic information. SNP mapping, determination of haplotype patterns in mitochondria DNA (mtDNA), locus control region (LCR) repeat-sequencing and Y-chromosomes can provide additional genetic information (3133).…”
Section: Discussionmentioning
confidence: 99%